High body mass index is not associated with increased treatment failure in infliximab treated pediatric patients with inflammatory bowel disease. Issue 3 (23rd November 2019) - Rodin, Isaac; Chan, Justin; Meleady, Laura; Hii, Clare; Lawrence, Sally; Jacobson, Kevan
Abstract : Background and Aim: While weight gain during infliximab therapy in inflammatory bowel disease (IBD) is common, there has been limited research evaluating its impact on infliximab efficacy. Methods: Primary aims of this study were to determine the frequency of excess weight gain (body mass index [BMI] > 25 kg/m 2 ) in children with IBD on maintenance infliximab and evaluate the impact on infliximab dosing, serum trough levels, and treatment failure. Secondary aims were to determine differences in weight gain, treatment characteristics, and clinical/biochemical variables between patients with therapeutic and subtherapeutic maintenance therapy trough levels. We performed a retrospective study of 253 pediatric IBD (75.1% Crohn's disease, 23.3% ulcerative colitis, 1.6% IBD‐unclassified) patients on infliximab followed at BC Children's Hospital between January 2013 and January 2018. Results: Median age at infliximab initiation was 13.9 years, median length of follow up was 56.9 months, and 55.7% were males; 10.3% of the cohort demonstrated excess weight gain (7.5% overweight, 2.8% obese). Average mg/kg dosing was not statistically different between groups (normal, overweight, and obese: 6.7, 6.4, and 6.7 mg/kg, respectively, P = 0.52). Median BMI of patients with therapeutic and subtherapeutic trough levels was similar at 19.9 kg/m 2 (interquartile range [IQR], 17.3–23.8) and 19.7 kg/m 2 (IQR, 17.4–21.9), respectively. BMI had no effect on secondary loss of response to infliximab, with no significant difference between normal and high BMI subgroups (13.4 vs. 16.7%, P = 0.9). Conclusions: In a subgroup of pediatric IBD patients on maintenance infliximab, excess weight gain was not associated with higher weight‐based dosing, lower serum trough levels, or increased risk of treatment failure. Abstract : In a subgroup of pediatric inflammatory bowel disease patients on maintenance infliximab, 10.3% of the cohort demonstrated excess weight gain. This gain was not associated with higher weight‐based mg/kg dosing, lower serum trough levels, or increased risk of treatment failure.